Preferensi dan Perilaku Tokoh Masyarakat terhadap Perbankan Syariah di Kecamatan Sungai Pagu Kabupaten Solok Selatan - Anisah, Ariyun; Widianita, Rika; Nurani, Khadijah (Al-bank: Journal of Islamic Banking and Finance, 2021)
The development of Islamic banking in the Sungai Pagu sub-district of South Solok Regency┬á in terms of network operations, where the Bank Syariah Services Unit in Nagari Muaralabuh is the only Islamic banking institution operating in this area. The problem in this study is: What are the preferences and behavior of community leaders on Islamic banking in Sungai Pagu District.With the aim of knowing the preferences and behavior of community figures on Islamic banking in Sungai Pagu district, South Solok Regency. This research is a field study with a qualitative descriptive approach. Primary data sources are community figure involved┬á in BAMUS Nagari management of 55 people selected with purposive sampling techniques. Data collection techniques are conducted┬á through interviews, observations, questionnaires, and documentation. The results revealed the preferences of respondents in the banking sector in Sungai Pagu district, South Solok Regency, with a percentage index above 60%, but this was not supported by good behavior from correspondents where the score index was below 60%. While the role of respondents in delivering and disseminating Islamic banking to the community is at 60%, meaning that good and community leaders are a medium of socialization and promotion of Islamic banking in this area